Perceptions of stakeholders regarding Education related Corporate Social Investment projects within a Human Rights-based approach : a case study of an Eastern Cape Education District Project - Lombard, A. (Antoinette) (University of Pretoria, 2018)
The South African business codes of Broad Based Black Economic Empowerment (BBB-EE) encourage businesses to be actively involved in closing the socio-economic divide. Through a variety of levels of involvement, businesses intervene within chosen communities to address societal challenges. A case study of one such business in the Eastern Cape was explored in this study. The goal of the study was to explore and describe the perceptions of stakeholders regarding education related corporate social investment (CSI) projects within a human rights-based approach in an Eastern Cape Education District Project. The study embraced a qualitative research approach. The purpose of the research was exploratory and descriptive, and the design used was that of a case study. The sample for the study was selected purposively and included nine participants made up of five teachers, one principal, one vice-principal, and two education district officials. The data was derived through semi-structured one-on-one interviews and was analysed by thematic analysis, as outlined by Creswell (2014:197). The findings showed that CSI is creating an opportunity for bridging educational gaps in the current South African system. Departments, teachers, and learners alike are benefiting from the funding and skills that are being concerted by companies – contributing to empowerment and the preservations of human rights. The study concludes that a lack of knowledge around human rights, shortage of skills and the sparsity of opportunities that allow for continual professional development amongst teachers as well as ineffective communication within multiple service providers hinder the full extent of the preservation of human rights within the education sector. Recommendations include the need for a stronger emphasis on human rights and their practical application within rural schools, the need for continuous training for teachers, and platforms for effective communication within the educational system. Furthermore, CSI projects also need to be intentional regarding operating within systems and networks of multiple service providers and stakeholders.